Breast Self Examination, Health Belief, Knowlegde, Practice, and their Predictors Among Rural Malay Women in Kedah, Malaysia - Mohd Khairi, Umi Zarifah (2011)
Introduction: Malaysian women have 1 in 20 chances of developing breast cancer in their life time. The late stage at diagnosis was remarked as attributable to mortality rate. This is due to the less effective treatment received and low survival rate. Breast Self Examination (BSE) as early detection method was featured as important to encourage women particularly in rural area to be more breast health aware. However, based on the Second and Third National Health Morbidity Survey, BSE practice was remaining low especially among rural women in Kedah. Therefore, there is a need to understand factors that may influence the BSE practice among these women. Objective: To examine the relationship of beliefs and knowledge to BSE practice among rural women in Kedah. Methods: A cross sectional study was done based on random sampling method. Participants were Malay, had not had breast cancer or other breast disease and were not currently pregnant or breastfeeding. The questionnaire consists of sociodemographic background, knowledge and the Malay version of Champion’s Health Belief Model Scale (CHBMS). Chi square test, t test and logistic regression analysis were performed throughout the data analysis. Level of significance for all statistics was set at p< 0.05. Findings: The prevalence of monthly BSE practice was only 13.1%. There are significant relationship between BSE practice and age, level of education and knowledge on breast cancer and BSE. The mean scores for perceived benefits (t= 16.097, p<0.001) and confidence (t= 8.236, p<0.001) were noticeably higher in performers but lower in terms of barriers to BSE (t= 11.306, p<0.001). Logistic regression analysis indicated that women who perceived more benefits of BSE (OR=1.327, 95% CI= 1.212-1.453) and confident in ability to perform BSE (OR= 1.071, 95% CI= 1.024-1.120) as well as had higher knowledge on BSE (OR= 1.328, 95% CI= 1.080-1.633) and breast cancer symptoms (OR= 1.231, 95% CI= 1.061-1.428) were more likely to perform BSE. Conclusions: Findings from this study indicated that knowledge on BSE and breast cancer symptoms with perceived benefits and confident of BSE were the predictors of BSE practice among rural women in Kedah. Therefore, effective intervention program that emphasize self efficacy, benefits of BSE, knowledge particularly on BSE and breast cancer symptoms are recommended.